Reconstructing Research About Close Relationships in Old Age: A Contribution From Critical Gerontology - Piel, Julia; Robra, Bernt-Peter (Frontiers in Sociology, 2018)
Social studies on close relationship (CR) in old age of Western societies present the heterosexual couple as the dominant model of the late CR. Researchers focus mainly on couples in long-term relationships living in a common household. But in Germany, for example, only about half of all men and women between the ages of 65 and 75 live in a marital heterosexual relationship (Federal Statistical Office, 2016). In addition to the increasing change in the bonding behavior of older people, a differentiated picture of CR is already emerging. Accordingly, there are a large number of people for whom other forms of living together in old age are important. In population statistics (multiple) re-married, same-gender or non-marital relationship models in old age are underrepresented although they are particularly relevant in modern societies, for example in East Germany and for younger generations. This article is a critical reflection on the heteronormative view of late-life CR in the current gerontological research that leads to marginalization of older people whose CR does not correspond to this ideal. Heteronormativity refers to the “assumption of two clearly distinguishable, mutually exclusive sexes” according to which heterosexual desire is regarded as natural and normal (Hartmann & Klesse, 2007, p. 7). With a de-constructionist approach the heteronormative foundation of scientific categories can be demonstrated using the example of two gerontological studies. A normativity-critical research practice (Estes, 2011, p. 314; Katz, 1996) can help to make the diversity of late CR visible and support realistic empirical findings in gerontology.